The Enhancing Effect of Focused Ultrasound on TNK-Tissue Plasminogen Activator-Induced Thrombolysis Using an In Vitro Circulating Flow Model - Papadopoulos, Nicos G.; Yiallouras, Christos; Damianou, Christakis A. (My University, 2016)
Background The limited efficacy of thrombolytic therapy in patients with ischemic stroke has created the need to use focused ultrasound (FUS) energy as a way to enhance thrombolysis efficacy (sonothrombolysis). Using an in vitro circulating flow model, we evaluated the role of physical parameters on tenecteplase (TNK-tPA)-mediated thrombolysis. Materials and Methods Fully retracted porcine blood clots were used for the proposed experimental study. To provide a more realistic clinical environment of stroke, the study was conducted under realistic flow conditions and TNK-tPA concentrations. Two spherically FUS transducers (4-cm diameter), focusing at 10 cm and operating at .6 and 1.05 MHz, respectively, were used. Pulsed ultrasound protocols that maintained a localized temperature elevation at the focus of 1°C were applied. Thrombolysis efficacy was measured in milligram of mass clot removed. Results The effect of physical parameters such as temperature, FUS frequency, acoustic power (AP), FUS energy, and microbubble (MB) administration on thrombolysis efficacy was examined. Conclusions Study findings established that higher FUS frequencies (1 MHz) are associated with enhanced thrombolysis compared to lower FUS frequencies (.6 MHz). Furthermore, an increase in the linear relationship between AP and thrombolysis efficacy was exhibited. Also, the outcome of the study showed that the combination of 1-MHz FUS pulses with MBs strongly enhanced the enzymatic thrombolytic efficacy of TNK-tPA, because with 30 minutes of treatment, 1050 mg of clot was removed through nonthermal mechanisms. Taking into consideration that stroke is time dependent, this thrombolytic rate should be sufficient for timely recanalization of the occluded cerebral artery.
Keywords: TNK-tPA; Stroke; Thrombus; Ultrasound